Slovenian vodkinja ‘female leader’ - Peter Weiss (Jezikoslovni zapiski)
Standard Slovenian has a need for a feminine equivalent of the masculine noun vodja ‘leader’. After examining attempts to establish such a word or to simply use the masculine form for the feminine designation, the author suggests the form vodkinja, which is derived from the truncated masculine designation, like računovodkinja ‘female accountant’ (alongside računovodja for a male accountant), zborovodkinja ‘female choir director’ (alongside zborovodja for a male choir director), and similar.